Analysis of Role and Issues Relating to Agriculture Credit in India: An Overview - Fatehpuria, A; Parihar, M (International Journal of Computer Sciences and Engineering, 2025)
To ensure healthy and orderly growth of any sector in any economy an adequate, reasonably cheap and timely financial support or availability is a pre-requisite. Amongst all the sectors of our economy, Agriculture sector has always been the backbone of the India Economy. In other words, agriculture sector is a need of any economy for growth and development. It is widely recognized that in order to obtain all the benefits of agriculture in our economy, we need to strengthen our agriculture sector. However, in current context our agriculture sector is going through numerous problems relating to irrigation, productivity, technology, credit facility, labour issues, electricity, illiteracy, land holdings, government’s inadequate support, labour income, etc. Among all, the problem we come across many times that a farmer has committed suicide due to financial reasons. As we are aware of the fact that agriculture is one of the most important segment of our Economy with reference to supply of food grains, employment opportunities, supply of raw materials, etc., its share has declined in GDP over the period of time, from more than 55 per cent during 1951 to around 16 per cent or little more in current scenario. Although, various governments at different times during plans and policy period tried their best and putted ample efforts for growth and development of agriculture sector in our economy. However, despite many efforts and attempts to eliminate the issues relating to agriculture, the sector still faces lots of issues and challenges. Therefore, like other sectors of an Economy, Agriculture sector also needs a supportive system for its Growth and Development.